2016
DOI: 10.1177/1538574416647503
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Aneurysm Repair Increases Aortic Arterial Stiffness When Compared to Open Repair of Abdominal Aortic Aneurysms

Abstract: EVAR patients have a significantly higher postoperative PWV measurement than those undergoing open abdominal aortic aneurysm repair. Patients who have undergone EVAR may be at a higher risk of cardiovascular morbidity in the long term. A larger scale study with a longer prospective follow-up is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…However, there are contradictory data in the literature: Studies either do not show a postprocedural increase in PWV 32,33 or indicate a higher PWV elevation in the open repair group. 34 Obviously, there is a need for a more adequate investigation of this impact.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are contradictory data in the literature: Studies either do not show a postprocedural increase in PWV 32,33 or indicate a higher PWV elevation in the open repair group. 34 Obviously, there is a need for a more adequate investigation of this impact.…”
Section: Discussionmentioning
confidence: 99%
“…9 Literature is inconclusive about the effect of AAA on the cfPWV, but there is evidence for an increase in cfPWV after EVAR in the early phase after surgery, [10][11][12][13][14] and there is evidence that this increase is absent after open surgical aneurysm repair. 10,15 After EVAR, alterations in arterial stiffness and wave reflections might provide insight in the adverse effects on myocardial function and thereby whether these alterations might lead to the adverse cardiovascular risk profile on long term. Data are scarce on whether the initial increase after EVAR in PWV changes or stabilizes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with a study on 50 patients (39 with a graft-prosthesis and 11 with a stentgraft) by Lantelme et al, who suggested that stentgraft increases reflected waves, as recorded with carotid-femoral PWV, more than graft-prostheses. 26 Moreover, another study by Gray et al 27 reported a significantly higher postoperative PWV measurement than those undergoing open abdominal aortic aneurysm repair.…”
Section: Discussionmentioning
confidence: 98%